2015
DOI: 10.1007/s10815-015-0492-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of aneuploidy formation in human blastocysts resulting from donated eggs and the necessity of the embryos for aneuploidy screening

Abstract: Purpose To examine the prevalence of aneuploidy in human blastocysts resulting from donated eggs and embryo implantation after transfer of normal euploid embryos. Also, to assess the necessity of preimplantation genetic screening (PGS) for embryos produced with donor eggs. Methods Blastocysts from donor-recipient cycles were biopsied for PGS (PGS group) and the samples were analyzed with DNA microarray. Euploid blastocysts were transferred to the recipients, and both clinical pregnancy and embryo implantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
1
29
2
Order By: Relevance
“…The proportion of aneuploid embryos increases in women with aging [ 4 10 ]. Even in young patients undergoing in vitro fertilization (IVF), it has also been found that high proportions of embryos are aneuploid [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of aneuploid embryos increases in women with aging [ 4 10 ]. Even in young patients undergoing in vitro fertilization (IVF), it has also been found that high proportions of embryos are aneuploid [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously it has been found that PGS can increase clinical pregnancy and embryo implantation rates in patients of advanced maternal ages, recurrent miscarriage and previous spontaneous miscarriage, as aneuploidy is the main reason for unsuccessful embryo implantation in these populations of patients [ 9 , 18 20 ]. As widespread application of PGS in human IVF clinics, it would appear that PGS may also increase embryo implantation rate in all patients undergoing IVF including young patients and recipients who receive egg donation [ 9 , 10 , 12 , 14 , 19 ], especially when single embryo transfer is performed [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we did not find significant increase in either clinical pregnancy or embryo implantation when blastocysts from donated eggs were screened and transferred, especially when two blastocysts were transferred. As suggested by these authors, unrestricted clinical application of current PGS (either aCGH or NGS) should be avoided [ 30 , 31 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, egg donor cycles have resulted in transfer of PGT-untested embryos. While donor oocyte cycles typically result in high pregnancy and live birth rates due to the young age of the donor, prior studies have shown that up to one third of embryos derived from donor oocytes are aneuploid (41,42). In a retrospective cross-sectional study of U.S. data from the Society for Assisted Reproductive Technology Clinic Outcome Reporting System from 2005 to 2013, live birth rates were significantly lower for PGT-A (51.8%) than control cycles (59.9%, P¼ .001).…”
Section: Preimplantation Genetic Testingmentioning
confidence: 99%